2019
DOI: 10.1007/s00345-019-03025-w
|View full text |Cite
|
Sign up to set email alerts
|

Fewer tumour draining sentinel nodes in patients with progressing muscle invasive bladder cancer, after neoadjuvant chemotherapy and radical cystectomy

Abstract: Purpose To examine the relationship between the number of tumour draining sentinel nodes (SNs) and pathoanatomical outcomes, in muscle-invasive bladder cancer (MIBC), in patients undergoing neoadjuvant chemotherapy (NAC) and radical cystectomy (RC). Materials and Methods In an ongoing prospective multicenter study, we included 230 patients with suspected urothelial MIBC from ten Swedish urological centers. All underwent TURb and clinical staging. From the cohort, 116 patients with urothelial MIBC; cT2-cT4aN0M0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This finding is in accordance with similar studies in other malignancies [118,119]. More recent studies have assessed SLN techniques in various clinical settings and concluded that they are feasible and safe in BCa, although their efficacy remains questionable [120][121][122]. In 2022, Rietbergen et al initiated a prospective pilot study evaluating the usage of a hybrid ICG-99m Tc-nanocolloid radiotracer.…”
Section: Bladder Cancersupporting
confidence: 77%
“…This finding is in accordance with similar studies in other malignancies [118,119]. More recent studies have assessed SLN techniques in various clinical settings and concluded that they are feasible and safe in BCa, although their efficacy remains questionable [120][121][122]. In 2022, Rietbergen et al initiated a prospective pilot study evaluating the usage of a hybrid ICG-99m Tc-nanocolloid radiotracer.…”
Section: Bladder Cancersupporting
confidence: 77%
“…In a recent single center study, Zarifmahmoudi et al reported a SN detection rate of 85% and a false negative rate as high as 42% [ 26 ]. However, another MIBC study concluded that SN detection played no role in staging of nodal disease since the vast majority of LNM were detected in the non-sentinel lymph nodes [ 27 ]. The high number of false negatives would, therefore, lead to understaging if one does not proceed with PLND if the outcome of the SN is negative.…”
Section: Discussionmentioning
confidence: 99%
“…al's multicentre analysis which identified a higher average number of tumour-draining sentinel lymph nodes in patients treated with NAC who belonged to the Complete Response rather than the Progressive Disease cohort, thereby implying that the number of positive LNs is directly proportional to the strength of the immune system. 53 Conversely, whilst submission of separate nodal packets instead of en-block has shown a significant increase in total LN yield, this was not associated with an increased number of positive LNs, making LN density an inaccurate prognostic indicator. 54 Approximately 41% of metastatic lymph nodes are outside the confines of the standard PLND template, implying that an extended or super-extended PLND would yield superior oncological outcomes.…”
Section: Pelvic Lymph Node Dissectionmentioning
confidence: 99%